Implementation of the ars moriendi model in palliative home care: A pilot study. (1st November 2013) - Vermandere, Mieke; Bertheloot, Karen; Buyse, Hanne; Deraeve, Pieterjan; De Roover, Stijn; Strubbe, Liselot; Van Immerseel, Ilke; Vermandere, Stefanie; Voss, Mariska; Aertgeerts, Bert
<x xml:space="preserve">Abstract</x> Background Assessing the spiritual well-being of palliative patients is often perceived as difficult by professional caregivers. Previous research has shown that general practitioners would appreciate a directive for spiritual conversations, if this tool were not too structured and not too religious, and provided it proved to be useful in clinical practice. Aim To investigate the experiences of professional caregivers and patients with the ars moriendi model as a directive for spiritual conversations in palliative home care. Method Qualitative semi-structured interview pilot study in Flanders Results All professional caregivers (n = 7) experienced the ars moriendi model as a useful directive to talk about spirituality at the end of life. They stressed the importance of adjusting the questions to each patient, and of spreading the spiritual conversation over several contacts. The palliative patients (n = 4) appreciated the conversation and advised the caregivers to show an open attitude, to spend enough time on their spiritual well-being, and to follow them in their spiritual process. Both caregivers and patients emphasized the importance of a trusting relationship to establish spiritual conversations. Conclusion Flemish professional caregivers experienced the ars moriendi model as useful for supporting spiritual conversations, provided that the model is used in a spontaneous and intuitive way, according to the needs of the patient. Palliative patients are stimulated by the questions in the model to think about their spiritual needs and resources.